Visual studio 2010 best practices : learn and implement recommended practices for the complete software development life cycle with Visual Studio 2010 /: learn and implement recommended practices for the complete software development life cycle with Visual Studio 2010. (2012) - (Software consultant), Ritchie, Peter
No abstract available